Cognitive Outcome in Childhood-Onset Epilepsy: A Five-Decade Prospective Cohort Study. (10th January 2017) - Karrasch, Mira; Tiitta, Petri; Hermann, Bruce; Joutsa, Juho; Shinnar, Shlomo; Rinne, Juha; Anttinen, Anu; Sillanpää, Matti
Abstract: Objectives: Little is known about the very long-term cognitive outcome in patients with childhood-onset epilepsy. The aim of this unique prospective population-based cohort study was to examine cognitive outcomes in aging participants with childhood-onset epilepsy (mean onset age=5.3 years) five decades later (mean age at follow-up=56.5 years).Methods: The sample consisted of 48 participants with childhood-onset epilepsy and 48 age-matched healthy controls aged 48–63 years. Thirty-six epilepsy participants were in remission and 12 continued to have seizures. Cognitive function was examined with 11 neuropsychological tests measuring language and semantic function, episodic memory, and learning, visuomotor function, executive function, and working memory.Results: The risk of cognitive impairment was very high in participants with continuing seizures; odds ratio (OR)=11.7 (95% confidence interval [CI] (2.8, 49.6), p =.0008). They exhibited worse performances across measures of language and semantic function, and visuomotor function compared to participants with remitted epilepsy and healthy controls. In the participants with remitted epilepsy, the risk of cognitive impairment was somewhat elevated, but not statistically significant; OR=2.6 (95% CI [0.9, 7.5], p =.08).Conclusions: Our results showed that the distinction of continued versus discontinued seizures was critical for determining long-term cognitive outcome in childhood-onset epilepsy. Few participants in remission exhibited marked cognitive impairment compared to age-matched peers. However, a subgroup of participants with decades long active epilepsy, continuous seizure activity and anti-epileptic drug (AED) medication, showed clinically significant cognitive impairment and are thus in a more precarious position when entering older age. ( JINS, 2017, 23, 332–340)